Innovation in Making Cassava Opak-Opak with The Addition of Chicken Eggs on Nutritional Profile - Mulyani, Anisa; Bulkaini, Bulkaini; Yulianto, Wahid (Jurnal Biologi Tropis, 2025)
The North Lombok Regency Government continues to strive to increase cassava production. One effort to increase productivity is by creating a typical North Lombok food, namely opak-opak. The purpose of this study was to determine the nutritional profile of cassava opak-opak with the addition of broiler chicken eggs. This study used a Completely Randomized Design (CRD) with four treatments and five replications, with the addition of eggs of 0%, 5%, 10%, and 15% for each kilogram of cassava starch. The results showed significant changes in several chemical parameters of the product composition. Increasing the percentage of eggs from 0% (P0) to 15% (P3) had a significant effect on the moisture, ash, crude fat, crude fiber, and crude protein content of the final product. The moisture content decreased significantly after the addition of eggs at concentrations of 5% and 10% (P1 and P2), with values of approximately 2.89%, respectively, lower than the control without eggs (P0) which reached 4.26%. In the treatment with 15% eggs (P3), the water content increased again to 3.79%. The addition of eggs to the production of cassava opak-opak significantly affected the chemical composition (water content, ash, crude fat, crude fiber, and crude protein). Overall, the addition of 5% eggs per kilogram of cassava starch was the optimal formulation for producing opak-opak with the best chemical, functional, and sensory qualities.